HADIS-HADIS RUQYAH DAN PENGARUHNYA TERHADAP KESEHATAN MENTAL - Rohmansyah Rohmansyah; Muhammad Saputra Iriansyah; Fahmi Ilhami; Gilang Ari Widodo Utomo (Universitas Islam Negeri Ar-Raniry, 2018)
Rasulullah SAW-style treatment is a trend today is a ruqyah who not only treat physical diseases but also non-physical. Ruqyah is the solution the Prophet offered in overcoming all sorts of diseases, and ruqyah is allowed as long as it does not contain shirk elements. This study aims to explain the definition of ruqyah in the hadith of the Prophet, and the verses and prayers used at the time of ruqyah. Even explaining the existence of capitalist elements and the influence of ruqyah on mental health. This research uses the risearch library method using descriptive approach and socio-historical critique analysis to understand the hadith of the Prophet. The findings are: First, ruqyah is a treatment ala Rasulullah by taking refuge in Allah from all diseases both physical and non physical. Second, the way of ruqyah is by putting the right hand to the painful part of the limb while reading the reading of prayers, letters of al-Fatihah, al-Ikhlas, al-Falaq and al-Nas. Thirdly, the ruqyah should be based on a complete belief in God, pleading for protection to Him because He is the Essence that Heals all sicknesses. Fourth, ruqyah can give positive influence that is heal mental health or soul. Fifth, ruqyah is one of the solemn acts against the sickness of society which is far from Allah without capitalization by commercializing to serve as a livelihood in fulfilling the necessities of life except on the willingness of the patient or ruqyah sufferer by giving wages as a form of gratitude and meruqyah people may take wages by not looking at the size and size of the wage on the basis of sincere intentions.